HUBUNGAN ANTARA KELEKATAN (ATTACHMENT) ORANGTUA DENGAN KECENDERUNGAN REAKSI EMOSI ANAK PADA USIA 4-5 TAHUN DI PAUD KAISAH PALEMBANG - Popi Popira; Amir Hamzah; Elsa Cindrya (Jurnal Genta Mulia, 2024)
This study aims to determine whether there is a relationship between parental attachment and the tendency for children's emotional reactions at the age of 4-5 years at PAUD Kaisah Palembang. This type of research is quantitative correlation. The research sample used in this research was class A at PAUD Kaisah Palembang, totaling 15 children. The method for collecting data is a questionnaire with data analysis using the normality test, linearity test and hypothesis testing using the product moment correlation formula. The results of the hypothesis test data analysis with product moment correlation were obtained tcount > ttable, namely 0.997 > 0.514 which is in the value between tcount > ttable, namely 0.997 > 0.514 which is in the value between 0.80 – 1.000 (very strong) which means Ha is accepted so the hypothesis test results which has previously been suspected, the truth has been tested, meaning that there is a relationship between parental attachment and the tendency for children's emotional reactions at the age of 4-5 years at PAUD Kasih Palembang.